Age Evolution of Lipid Accretion Rate in Boars Selected for Lean Meat and Duroc Barrows - Laura Sarri; Joaquim Balcells; Ahmad Reza Seradj; Ramona N. Pena; Gustavo A. Ramírez; Marc Tor; Gabriel de la Fuente (Animals, 2022)
Fatty acid (FA) deposition in growing–fattening pigs is mainly based on endogenous lipid synthesis, but also direct FA incorporation from the diet. To evaluate the direct fat incorporation rates and the endogenous desaturation action of the stearoyl-CoA desaturase (SCD) enzyme, a deuterium (D)-labeled saturated FA (d35-C18:0) was added to the diet. Sixteen three-way (3W) crossbred boars, and thirty-two purebred Duroc barrows homozygous for the SCD single nucleotide polymorphism rs80912566 (16 CC/16 TT), were used. Half of the animals of each genotype belonged to the growing and fattening phases. The fractional incorporation rate (FIR) of dietary fat in growing pigs was generally higher in adipose tissues, whereas in fattening pigs it was higher in the liver. Duroc pigs exhibited lower FIRs than 3W pigs, suggesting lower rates of endogenous synthesis by 3W pigs. Real fractional unsaturation rates (FURs) increased with age by the higher FIRs in 3W pigs and the de novo synthesis pathway in Duroc genotypes. Moreover, pigs carrying the SCD_T allele showed more enhanced oleic acid biosynthesis than Duroc CC pigs. In conclusion, suitable feeding protocols should be designed for each pig type to optimize production traits, considering that the metabolic pathway of FA for its deposition may differ.